The Influence of Social Media Cigarette Advertising on Adolescent Smoking Behavior - Salsabila Syah; Samsiana; Nur Inayah Ismaniar (CV. Science Tech Group, 2026)
Smoking behavior among adolescents remains a serious public health issue in Indonesia. Social media has become a new platform for tobacco companies to indirectly promote their products through engaging content and influential public figures, potentially increasing adolescents' interest in trying cigarettes. This study aimed to analyze the relationship between exposure to cigarette advertisements on social media and adolescent smoking behavior in Banrimanurung Village, Jeneponto Regency. A quantitative research design with a cross-sectional approach was employed. The population consisted of 171 male adolescents, with 120 respondents selected through purposive sampling. Data were collected using a closed-ended questionnaire and analyzed using SPSS software with the Chi-Square test. The results showed a significant relationship between exposure to cigarette advertisements on social media and smoking behavior, with a p-value of <0.001 (<0.05). Exposure to cigarette advertisements on social media is therefore significantly associated with smoking behavior among adolescents in Banrimanurung Village. Increased awareness of smoking risks, stronger family and school supervision, and enhanced health promotion by community health centers are recommended. Moreover, reducing adolescent smoking through stricter digital advertising regulation not only protects individual health but also contributes to reducing environmental tobacco smoke (ETS) exposure in public spaces, decreasing cigarette butt waste — a major source of plastic and toxic pollution — and lowering the overall environmental burden of tobacco production and disposal, aligning with SDG 3 (Good Health and Well-being) and SDG 12 (Responsible Consumption and Production).